Anxiety, health-related quality of life, and symptoms of burnout in frontline physicians during the COVID-19 pandemic - Chalhub,Ricardo Ávila (2021)
ABSTRACT Background: COVID-19 pandemic caused increased workload and stress for health professionals involved in the care of such patients. We aimed to describe the health-related quality of life, and burnout in frontline physicians diagnosed with anxiety during the COVID-19 pandemic. Methods: This was a cross-sectional study conducted during the first-wave phase of COVID19, from September to October 2020. Questionnaires were sent electronically to 450 physicians from State of Bahia, assessing symptoms of anxiety, health-related quality of life (HRQOL) and burnout syndrome. For the categorical variables, the Pearson’s chi-square test was used and difference between means was compare using the Mann-Whitney test. was Groups with and without anxiety symptoms were compared using prevalence ratios (PR). Pearson’s correlation measured the correlation between WHOQOL-BREF and MBI (Maslach Burnout Inventory) domains. The Fisher r-to-z transformation was used to assess the significance of the difference between two correlation coefficients. The significance level was <0.05. Results: Out of the 450 physicians, 223 (49,6%) completely answered the questionnaire and 38 (17%) showed symptoms of anxiety. Physicians with anxiety had higher scores in emotional exhaustion (EE) (38.31 ± 8.59 vs 25.31±0.87; p = 0.0001) and depersonalization (DP) (9.0 ± 5.6 vs 5.9 ± 5.3; p = 0.001) domains, and lower scores in personal accomplishment (PA) (32.1 ± 8.2 vs 36.3 ± 7.6; p = 0.004), than those without anxiety. All correlations between WHOQOL-BREF domains and MBI in physicians without anxiety were significant (p = 0.01). Conclusion: Physicians with anxiety showed more emotional exhaustion, less personal accomplishment, and lower quality of life. All domains of WHOQOL BREF were correlated with all MBI domains among physicians without anxiety. Differences in correlation according to anxiety were remarkable in psychological HOQOL BREF domain and emotional exhaustion and depersonalization MBI domains. The effect of anxiety leading to poorer levels of perceived health needs to be further investigated.